2021
DOI: 10.1101/2021.02.17.21251558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping brain structural differences and neuroreceptor correlates in Parkinson’s disease visual hallucinations: a mega-analysis

Abstract: Parkinson's psychosis (PDP) describes a spectrum of symptoms that may arise in Parkinson's disease (PD) including visual hallucinations (VH). Imaging studies investigating the neural correlates of PDP have been inconsistent in their findings, due to differences in study design and limitations of scale. Here we use empirical Bayes harmonisation to pool together structural imaging data from multiple research groups into a large-scale mega-analysis, allowing us to apply new methodological approaches to identify c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 80 publications
1
7
4
Order By: Relevance
“…Presumably, the development of psychosis in PD patients could then be due to dysfunction in networks involved in attention control and visual information processing (Lenka et al, 2015;Muller et al, 2014;Shine et al, 2011;Shine, O'Callaghan, et al, 2014) that become pathological due to grey matter reduction in their nodes, as shown in the meta-analysis results, which consequently leads to abnormal functionality at a network level. Our results are to some extent different from those of the mega-analysis (Vignando et al, 2021) and may be due to the diverse methodologies used (mega-analysis vs.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Presumably, the development of psychosis in PD patients could then be due to dysfunction in networks involved in attention control and visual information processing (Lenka et al, 2015;Muller et al, 2014;Shine et al, 2011;Shine, O'Callaghan, et al, 2014) that become pathological due to grey matter reduction in their nodes, as shown in the meta-analysis results, which consequently leads to abnormal functionality at a network level. Our results are to some extent different from those of the mega-analysis (Vignando et al, 2021) and may be due to the diverse methodologies used (mega-analysis vs.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with Vignando et al (2021) who found associations with dopaminergic receptor density with cortical thickness in regions where PDP and PDnP had significant differences, and with surface area for significant regions of difference as well as across the cortex. However, we were only able to extract data on D1/D2 receptors unlike Vignando et al (2021) who investigated the relationship with D2/D3 joint receptor density distribution. This discrepancy may also be due to methodological differences: they used mean thickness differences as the outcome variable, whilst we employed Hedges' g effect-size estimates extracted from SDM-PSI used as a measure of grey matter loss in PDP patients, lastly they examined in-vivo PET data from an independent healthy cohort whilst we relied on gene expression data extracted from six healthy donors of the Allen Human Brain Atlas (Arnatkevic̆iūtė et al, 2019;Desikan et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations